Optimization Analysis of CO2 Refrigeration and Heat Recovery System for Ice Rink Based on Pinch Point Theory - Zhou Xiaohu; Geng Xudong; Li Feng; Si Chunqiang; Ma Jin; Shao Shuangquan (Zhileng xuebao)
Against the backdrop of carbon neutralization, CO2 has attracted increasing attention as a natural working medium for refrigeration and heating applications. Based on pinch point analysis, a CO2 refrigeration and heat recovery system for an ice rink is optimized and analyzed. Under the assumption of two-stage heat recovery (water temperatures at the inlet and outlet are 40 °C and 60 °C for low-temperature heat recovery and 60 °C and 80 °C for high-temperature heat recovery), the following results were obtained by changing the water mass flow rate at a specific stage. The existence of the pinch point increased the CO2 outlet temperature for heat recovery in the heat exchanger and reduced the amount of recovered heat, heating coefficient of performance (COPh), and comprehensive COP of the system. The optimal discharge pressure corresponding to the maximum COP also moved backward until it exceeded the upper limit. When the mass flow ratio of the second stage is 0.4, the influence of the pinch point can be eliminated by adjusting the mass flow ratio of the first stage. When the mass flow ratio of the first stage is 0.4, the optimal discharge pressure increased from 10.2 to 10.9 MPa, while the maximum comprehensive COP decreased from 3.538 to 2.843. To improve the system performance, the mass flow rate of water at the second and first stages should be decreased and increased, respectively, while the discharge pressure should be increased within a reasonable range.